Environmental, Social, and Governance (ESG) Performance and Economic Growth: An Econometric Analysis for Central European Countries - Nikqi, Liridona (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This study analyzes the impact of environmental, social, and governance (ESG) performance on economic growth in Central European countries. Using an econometric approach, the study assesses ESG indicators’ contribution to economic development and examines whether these factors drive sustainable growth. A scientific methodology based on secondary data from the World Bank’s annual reports was applied. Several econometric models, including multiple linear regression, random effects, fixed effects, Hausman-Taylor regression, GMM, and GEE models, were used. The results show a strong relationship between ESG performance and economic growth. Governance effectiveness and corruption control positively impact GDP growth, while increasing CO2 emissions negatively affect it. Similarly, investments in education and health contribute to long-term growth, emphasizing the importance of sustainable development policies. This research presents reliable results supporting conclusions and recommendations.